2022
DOI: 10.18632/aging.204266
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics treatment for Parkinson disease: a systematic review and meta-analysis of clinical trials

Abstract: Background and aims: People with Parkinson disease (PwP) exhibit gut dysbiosis and considerable gastrointestinal (GI) symptoms. Probiotics, beneficial strains of microorganisms, supplement and optimize the intestinal environment and alleviate GI symptoms among elderly people. We conducted a systematic review and metaanalysis of clinical trials to investigate the effects of probiotics on PwP. Methods: We searched the PubMed, Embase, and Cochrane Library databases. Major outcomes were the effects on GI symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
0
7
0
1
Order By: Relevance
“…Interestingly, two RCTs that examined the use of laxatives during probiotic intake in patients with PD found that probiotic intake significantly decreased the use of laxatives (SMD = −0.27; 95% CI, −0.53, −0.01; P < 0.04; I 2 = 15%). A previous meta-analysis that included three RCTs also revealed that oral supplementation with probiotics markedly increased the frequency of bowel movements (mean difference [MD]:1.06 per week, 95% CI:0.61 to 1.51, p < 0.001, I 2 = 40%) and improved stool consistency (standard MD:0.61, 95% CI = 0.31 to 0.91, p < 0.001, I 2 = 0%), 22 which is consistent with the findings of our meta-analysis. The effects of probiotics on functional constipation in adults without PD have been extensively investigated.…”
Section: Food and Function Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, two RCTs that examined the use of laxatives during probiotic intake in patients with PD found that probiotic intake significantly decreased the use of laxatives (SMD = −0.27; 95% CI, −0.53, −0.01; P < 0.04; I 2 = 15%). A previous meta-analysis that included three RCTs also revealed that oral supplementation with probiotics markedly increased the frequency of bowel movements (mean difference [MD]:1.06 per week, 95% CI:0.61 to 1.51, p < 0.001, I 2 = 40%) and improved stool consistency (standard MD:0.61, 95% CI = 0.31 to 0.91, p < 0.001, I 2 = 0%), 22 which is consistent with the findings of our meta-analysis. The effects of probiotics on functional constipation in adults without PD have been extensively investigated.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…Currently, as far as we know, we only found a similar meta-analysis, but this study only included three RCTs. 22 The certainty of evidence was graded as very low. Therefore, in this study, we performed a meta-analysis of RCTs to examine the effects of probiotics in patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Tamtaji et al identified that probiotics ( Lactobacillus acidophilus , Bifidobacterium bifidum , and Bifidobacterium longum , 2 × 10 9 CFU/day) combined with selenium supplementation significantly enhanced cognitive function compared to selenium or placebo alone in AD patients [ 126 ]. Administration of probiotic Lactobacillus and Bifidobacterium strains alleviated both constipation symptoms and motor symptoms in PD patients [ 127 , 128 ]. However, a meta-analysis that included trials investigating the effects of probiotics, mainly Lactobacillus and Bifidobacterium , did not find any beneficial effects on cognitive function in diagnosed AD patients [ 129 ].…”
Section: Potential Clinical Approaches Targeting the Microbiome In Ndsmentioning
confidence: 99%
“…In vivo studies report improved glucose metabolism, reduced inflammation, and neurodegeneration (Leta et al, 2021). In a review of eight clinical trials in PD patients given lactobacilli or bifidobacteria probiotics (Hong et al, 2022), constipation was significantly reduced, and modest anti-inflammatory effects were observed. A downside of using probiotics in PD is the potential for probiotic-drug interactions since bacterial decarboxylases may affect the bioavailability of -dopamine, a Carbidopa component commonly used to manage PD neurological symptoms (van Kessel et al, 2019).…”
Section: Intestinal Phenotype Hypothesismentioning
confidence: 99%